Advanced oxidation in the treatment of microplastics in water: A Review - Yalin Ma; Kaibo Jin; Xiuhai Yin; Xusheng Zhao; Zhenduo Liu; Yanyan Dou; Tianyu Ao; Yang Li; Xuejun Duan (Desalination and Water Treatment)
In recent years, microplastics, as emerging contaminants, have raised global concern among scholars due to their potential threats to both ecological systems and human health. Traditional water treatment methods primarily remove microplastics through phase transfer mechanisms, which fail to achieve actual degradation. In contrast, Advanced Oxidation Processes (AOPs) demonstrate superior efficacy by generating reactive free radicals that degrade microplastics efficiently. Remarkably, AOPs can even mineralize microplastics into harmless CO₂ and water, positioning them as a forefront research focus for microplastic remediation. This paper systematically reviews applications of various AOPs, including UV/UV-H₂O₂ oxidation, O₃/O₃-H₂O₂ oxidation, UV-induced photocatalysis, solar/visible light-induced photocatalysis, electrochemical oxidation, and persulfate oxidation, in degrading aqueous microplastics. The degradation efficiencies, mechanistic pathways, and reaction kinetics are critically analyzed, alongside a comparative assessment of each technique's advantages and limitations. Finally, the review discusses future prospects and challenges for implementing AOPs in microplastic treatment.